Mutation of mtDNA ND1 Gene in 20 Type 2 Diabetes Mellitus Patients of Gorontalonese and Javanese Ethnicity - AMIEN RAMADHAN ISHAK; RINI PUSPITANINGRUM; RISMA DWI UTARI; MELLA FERANIA; CHRIS ADHIYANTO; TAKENORI NITTA; AB SUSANTO; HATTORI YUKIO; YASUHIRO YAMASHIRO (Bogor Agricultural University, Indonesia, 2014)
Mitochondrial gene mutation plays a role in the development of type two diabetes mellitus (T2DM). A point mutation in the mitochondrial gene Nicotinamide adenine dinucleotide dehydrogenase 1 (mtDNA ND1) gene mainly reported as the most common mutation related to T2DM. However, several studies have identified another SNP (single-nucleotide polymorphisms) in the RNA region of mtDNA from patients from specific ethnic populations in Indonesia. Building on those findings, this study aimed to use PCR and DNA sequencing technology to identify nucleotides in RNA and ND1 fragment from 20 Gorontalonese and 20 Javanese T2DM patients, that may trigger T2DM expression. The results showed successful amplification of RNA along 294 bp for all samples. From these samples, we found two types of point mutation in Javanese patients in the G3316A and T3200C points of the rRNA and ND1 gene. In samples taken from Gorontalonese patients, no mutation were found in the RNA or ND1 region. We conclude that T2DM was triggered differently in our two populations. While genetic mutation is implicated for the 20 Javanese patients, T2DM pathogenesis in the Gorontalonese patients must be traced to other genetic, environmental, or behavioral factors.